영어교사 의사소통능력 향상을 위한 연수시간 요구도와 교사변인 연구 - 권선희(Kwon Sun-Hee) (영어어문교육, 2010)
The goals of the present study are two-fold: 1) to examine NNS teachers' needs for training period in improving their general communicative competence and classroom communicative competence, and 2) to explore the relationships of teachers' needs for the training period, and their current levels of general/classroom communicative competence and other background variables. Data was collected from seventy primary and secondary school English teachers (N=70) who participated in the six-month intensive teacher training program in South Korea. The teacher trainees responded to four questionnaires of 1) the self-diagnosis of their current levels of four language skills (L/S/R/W) in both general/classroom communicative competence, 2) the training period required to improve their general/classroom communicative competence for teaching both English and other subjects through English, 3) the period of their English teaching, and 4) the proportion of their English use in class. The data analysis has shown that there were the strong relationships between trainee needs for the training period and their teaching period, and the proportion of their English use in class. In terms of trainees' communicative competence, the significant relations of both their general/classroom communicative competence and their needs for the training period were found. Implications of the findings are discussed.